2013
DOI: 10.1097/aln.0b013e318275146d
|View full text |Cite
|
Sign up to set email alerts
|

Coadministration of Hydrogen Gas as Part of the Carrier Gas Mixture Suppresses Neuronal Apoptosis and Subsequent Behavioral Deficits Caused by Neonatal Exposure to Sevoflurane in Mice

Abstract: Background:In animal models, several anesthetics induce widespread increases in neuronal apoptosis in the developing brain with subsequent neurologic deficits. Although the mechanisms are largely unknown, the neurotoxicity may, at least in part, be due to elevated oxidative stress caused by mitochondrial dysfunction. In an investigation of potential therapies that could protect against this type of damage, we studied the effects of molecular hydrogen on anestheticinduced neurotoxicity in the developing mouse b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 43 publications
2
54
0
Order By: Relevance
“…The developing brain is particularly susceptible to oxidative stress damage due to its high oxygen consumption, high polyunsaturated fatty acid content, and low antioxidant defenses (Morrison et al, 2013;Tiwari and Chopra, 2012). Accumulating evidence implies that the deleterious effects of general anesthetics on neuronal cells have been related to enhanced oxidative stress (Boscolo et al, 2012;Sanchez et al, 2011;Yonamine et al, 2013). It is well established that oxygen radicals can easily react with macromolecules, including DNA, lipids, and protein, and ultimately leading to cellular injury (Luo et al, 2013;Tiwari and Chopra, 2012).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The developing brain is particularly susceptible to oxidative stress damage due to its high oxygen consumption, high polyunsaturated fatty acid content, and low antioxidant defenses (Morrison et al, 2013;Tiwari and Chopra, 2012). Accumulating evidence implies that the deleterious effects of general anesthetics on neuronal cells have been related to enhanced oxidative stress (Boscolo et al, 2012;Sanchez et al, 2011;Yonamine et al, 2013). It is well established that oxygen radicals can easily react with macromolecules, including DNA, lipids, and protein, and ultimately leading to cellular injury (Luo et al, 2013;Tiwari and Chopra, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Mounting evidence from animal studies shows that anesthetic exposure in early life leads to neuroapoptosis in the developing nervous system, where loss of neurons is associated with behavioral deficiencies later in life (Shen et al, 2013a,b;Yonamine et al, 2013). We examined cleaved caspase-3 expression to represent apoptosis in the prefrontal cortex and hippocampus, two key brain regions involved in the memory processes, and we confirmed that anesthesia with 3% sevoflurane for 2 h daily for 3 days in P6 mice increased caspase-3 activity, while preadministration of curcumin decreased neuroapoptosis and alleviated the cognitive impairment.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Accumulating evidence has suggested drugs that block Nmethyl-D-aspartate (NMDA) receptors and/or activation of gamma-aminobutyric acid receptors can cause widespread neuroapoptosis in the developing brain and result in subsequent long-term neurobehavioral abnormalities later in life [1,23]. Sevoflurane is an inhalation anesthetic commonly used in obstetric or pediatric surgery and has been shown as a NMDA receptor antagonist [1].…”
Section: Discussionmentioning
confidence: 99%